2012
DOI: 10.1111/j.2042-7158.2012.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cytochrome P450 mediates interaction between warfarin and Coleus forskohlii extract in vivo and in vitro

Abstract: CFE attenuates the anticoagulant action of warfarin by inducing hepatic CYP2C; thus, caution is required with the combination of warfarin and dietary supplements containing CFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…In the present study in rats, we observed an interaction of CFE with tolbutamide in vivo, in terms of hypoglycemia and induction of hepatic CYP2C. The present findings are similar to those concerning the interaction of warfarin and CFE in our previous study in mice 12) . CFE induced hepatic CYP3A-type enzymes as well as CYP2C, and these two forms of CYP catalyze the metabolism of about 70 of prescription drugs 19), 20) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study in rats, we observed an interaction of CFE with tolbutamide in vivo, in terms of hypoglycemia and induction of hepatic CYP2C. The present findings are similar to those concerning the interaction of warfarin and CFE in our previous study in mice 12) . CFE induced hepatic CYP3A-type enzymes as well as CYP2C, and these two forms of CYP catalyze the metabolism of about 70 of prescription drugs 19), 20) .…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, we showed that feeding CFE to mice markedly increased the total content and activities of hepatic CYPs, and the estimated effective dose of CFE was comparable to the intake from a commercially available dietary supplement 11) . We also reported that CFE attenuated the anticoagulant action of warfarin via induction of hepatic CYP2C, an enzyme involved in metabolism of active (S)-warfarin, and CFE dose-dependently inhibited CYP2C activity in human and mouse microsomes in vitro 12) . These findings strongly suggested that CFE would interact with various prescribed drugs.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We speculated that the nature of the induction of drug-metabolizing enzymes by CFE is related to such a mechanism. As shown in our previous studies (19,21), CFE induced various drug-metabolizing enzymes such as CYP2B, CYP2C, CYP3A and GST, suggesting that the activation of transcription of drugmetabolizing enzymes is involved. Ding and Staudinger clearly showed that constituents of CFE, namely forskolin and 1,9-dideoxyforskoiln, induced CYP3A gene expression through the pregnane X receptor (PXR) in cultured hepatocytes (30).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that feeding mice a diet containing CFE (standardized with 10% forskolin) dose-and time-dependently induced hepatic CYPs and GST enzymes (19). Significant induction of the hepatic CYP content and CYP2C activity was evident at an intake dose of 0.05%; the CFE dose was 60 mg/kg body weight in mice and corresponded to about 5 mg/kg body weight of a human equivalent dose when calculated using the body surface normalization method (20 of warfarin and CFE in mice in vivo, where CFE attenuated the anticoagulant action of warfarin via induction of hepatic CYPs, especially CYP2C, which is involved in active (S)-warfarin metabolism (21). Furthermore, we showed that CFE induced CYPs in vivo and directly inhibited CYP2C activity in vitro as well.…”
mentioning
confidence: 99%